Career and life development intervention for non-engaged youth: Evaluating the Hong Kong Benchmarks (Community) Pilot Program - Ngai, Steven Sek-yum; Cheung, Chau-kiu; Zhou, Qiushi; Wang, Lin; Ng, Yuen-hang; Leung, Winnie Pui-ching; Yu, Elly Nga-hin; Wong, Laing-ming; Tang, Hon-yin; Lee, Horace Cheuk-him (Frontiers in Psychology, 2023)
In our study, aimed at examining the effectiveness and impact of the Hong Kong Benchmarks (Community) Pilot Program, a career and life development (CLD) intervention program targeting non-engaged youth (NEY) in Hong Kong, we employed a pretest–posttest quasi-experimental design to compare changes in career-related competencies between a pilot group (N = 289) and a comparison group (N = 160). We also conducted five focus group interviews with the leaders of nongovernmental organizations, social workers, NEY, parents, and employers to explore the program’s impacts on the CLD service provisions. Our quantitative results indicate that the piloting group showed greater improvement in two career-related competencies—youth career development competency and career and life development hope—than the comparison group. Meanwhile, our qualitative results suggest both the benefits and difficulties experienced by stakeholders in the program. The findings thus provide preliminary evidence of the Hong Kong Benchmarks (Community) Pilot Program’s positive impacts on NEY and other important stakeholders. The implications of expanding the existing program and theorizing the community-based benchmark approach are also discussed.